2021
DOI: 10.17336/igusbd.522024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Destination Image on the Perceived Value and Experience Quality: A Research on Cultural Tourists

Abstract: Bir turistik destinasyonun sahip olduğu olumlu imaj, o bölgenin aldığı turistik varış ve turizm gelirleri açısından büyük önem arz etmektedir. Olumlu bir imaj yaratabilmek stratejik bir karar olması dolayısıyla uzun vadeli bir süreci ifade etse de çıktıları buna değdiğini çarpıcı bir şekilde gözler önüne sermektedir. Özellikle sahip olunan pozitif imaj, deneyim kalitesi ve algılanan değer gibi turistik talebi önemli ölçüde etkileyebilecek birçok değişkenin de kontrol altında tutulmasını sağlamakta, hatta etkil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…When the academic studies on the quality of experience are examined, it is seen that the researched subjects are, satisfaction (Cole & Scott, 2004), satisfaction and behavioral intention (Cole and Illum, 2006), individuals' personal value judgments about a product or service (Yu & Fang, 2009), performance visitor management (Göktuğ & Yenilmez Arpa, 2015), perceived value and satisfaction, recommendation (Altunel & Günlü, 2015), loyalty and satisfaction (Fernandes and Cruz, 2016), life satisfaction, renewal experience (Yıldız et al, 2019), image of hotel businesses, guests' perception of value and repeating purchase intention (Çetiner & Yaylı, 2020), satisfaction, quality of life (Solunoğlu & Yayla, 2020) and destination image, perceived value (Akkuş & Şimşek, 2021). In the literature review on memorable tourism experiences, it was determined that there are researches in the subjects of feelings (Ruffolo and Servidio, 2016), loyalty behaviors (Kim, 2017), winter tourism (Akkuş, 2017), cultural tourism (Chen & Rahman, 2018), memorable trip (Güçlütürk Baran, 2019), entertainment, advice and revisiting intentions (Chen et al, 2020), customer satisfaction, intention to recommend and revisit intention (Keskin, et al, 2020;Ünal & Bayar, 2020), subjective well-being (Aydın & Ömüriş, 2020), psychological well-being (Karaca & Tağraf, 2021), and intention to revisit (Kahraman & Tanrıverdi, 2021) As a result of the examinations, no study was found in which the quality of experience and the memorable tourism experience were investigated together.…”
Section: Introductionmentioning
confidence: 99%
“…When the academic studies on the quality of experience are examined, it is seen that the researched subjects are, satisfaction (Cole & Scott, 2004), satisfaction and behavioral intention (Cole and Illum, 2006), individuals' personal value judgments about a product or service (Yu & Fang, 2009), performance visitor management (Göktuğ & Yenilmez Arpa, 2015), perceived value and satisfaction, recommendation (Altunel & Günlü, 2015), loyalty and satisfaction (Fernandes and Cruz, 2016), life satisfaction, renewal experience (Yıldız et al, 2019), image of hotel businesses, guests' perception of value and repeating purchase intention (Çetiner & Yaylı, 2020), satisfaction, quality of life (Solunoğlu & Yayla, 2020) and destination image, perceived value (Akkuş & Şimşek, 2021). In the literature review on memorable tourism experiences, it was determined that there are researches in the subjects of feelings (Ruffolo and Servidio, 2016), loyalty behaviors (Kim, 2017), winter tourism (Akkuş, 2017), cultural tourism (Chen & Rahman, 2018), memorable trip (Güçlütürk Baran, 2019), entertainment, advice and revisiting intentions (Chen et al, 2020), customer satisfaction, intention to recommend and revisit intention (Keskin, et al, 2020;Ünal & Bayar, 2020), subjective well-being (Aydın & Ömüriş, 2020), psychological well-being (Karaca & Tağraf, 2021), and intention to revisit (Kahraman & Tanrıverdi, 2021) As a result of the examinations, no study was found in which the quality of experience and the memorable tourism experience were investigated together.…”
Section: Introductionmentioning
confidence: 99%